2017
DOI: 10.1063/1.5001960
|View full text |Cite
|
Sign up to set email alerts
|

Orientational cross correlations between entangled branch polymers in primitive chain network simulations

Abstract: Although it has not been frequently discussed, contributions of the orientational cross-correlation (OCC) between entangled polymers are not negligible in the relaxation modulus. In the present study, OCC contributions were investigated for 4- and 6-arm star-branched and H-branched polymers by means of multi-chain slip-link simulations. Owing to the molecular-level description of the simulation, the segment orientation was traced separately for each molecule as well as each subchain composing the molecules. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…For the efficiency of SHAB, the relation between τ bb and τ w is essential. 40 For the small N a chains (with N a ≤ 17), SHAB occurs before the long arm relaxation (because τ bb > τ w ). On the contrary, for the large N a chains for which τ bb < τ w , SHAB never contributes to the long chain relaxation, which is dominated by the arm retraction and the dilation of the network.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the efficiency of SHAB, the relation between τ bb and τ w is essential. 40 For the small N a chains (with N a ≤ 17), SHAB occurs before the long arm relaxation (because τ bb > τ w ). On the contrary, for the large N a chains for which τ bb < τ w , SHAB never contributes to the long chain relaxation, which is dominated by the arm retraction and the dilation of the network.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Because of the neglected degrees of freedom between entanglements, this model attains a considerable reduction in computational costs, yet it naturally implements some multichain effects such as thermal and convective constraint release. This model has reproduced a variety of rheological phenomena for branch polymers semiquantitatively for linear and nonlinear viscoelasticity of star, , H, , pom-pom, and comb polymers. However, the problem of this modeling is that the molecular motion is calculated concerning the dynamics of entanglement, and thus, extensions toward further complex systems with specific intermolecular interactions are fundamentally challenging due to the lack of the requisite degree of freedom.…”
Section: Introductionmentioning
confidence: 99%
“…Masubuchi et al [33] reproduce the probe rheology data reported by Matsumiya et al [30] using primitive chain network (PCN) model, which describes the dynamics of the network formed by the primitive chains and is used extensively in literature [34][35][36][37][38]. Their results agree with the experiment well.…”
Section: Introductionmentioning
confidence: 61%
“…Vice versa, if the number of Kuhn segments on the dangling end exceeds a certain maximum, a new slip-link is created on the dangling segment to hook another segment from the surroundings randomly. The model has been extended to branch polymers with the implementation of the arm retraction and the branch point withdrawal 18,[24][25][26][27][28] . The calculated polymer dynamics and the resultant rheology are consistent with experiments for various entangled polymers, as reported previously.…”
Section: Model and Simulationsmentioning
confidence: 99%